Methodology for the design of the method of siliceous sandstones operation using special software - Lara-González, Luis Ángel; Cubides-Medina, César Augusto; Hernández-Buitrago, Edgar Rodrigo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
The methodologies used for the design of the method of sandstones explotation by descending staggered banks using specialized software tools are reported. The data analyzed were collected in the field for the operating license 14816 in Melgar, Tolima. The characterization of the rock mass was held from physical and mechanical tests, performed on cylindrical test tubes in order to obtain the value of the maximum strenght and elastic modulus of the rock. The direction and dip of the sandstone package was rock. The direction and dip of the sandstone package was determined by using the stereographic projection whit DIPS®  software, and the safety factor of the slope was obtained with established banks whit SLIDE® . The slops are 8 meters high and 8 meters wide whit a tilt angle 60°, which generated a safety factor  of 2.1. The design  of the mining method was carried out with GEOVIA SURPAC® , at an early stage of development ascending to the level 11 of the exploitation, to then start mining in descending order to control the stabiLity of slopes. The results obtained allow a general methodology for the development of projects to optimize the process of evaluation and selection of mining method by using specialized design tools.